# What is the second derivative of y=e^5x+(lnx)/2x ?

Rylan Hills | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

We have to find the second derivative of y = e^5x + (ln x) / 2x

y = e^5x + (ln x) / 2x

=> y = e^5x + (1/2)(ln x)*(1/x)

y' =...

(The entire section contains 76 words.)

check Approved by eNotes Editorial

giorgiana1976 | Student

To determine the second derivative, we'll have to determine the 1st derivative, for the beginning. We'll differentiate y with respect to x.

dy/dx = d(e^5x+(lnx)/2x)/dx

We'll apply chain rule for the first term of the sum and the quotient rule for the 2nd terms of the sum.

dy/dx = 5e^5x + [(lnx)'*2x - (lnx)*(2x)']/4x^2

dy/dx = 5e^5x + (2x/x - 2lnx)/4x^2

dy/dx = 5e^5x + 2(1 - lnx)/4x^2

dy/dx = 5e^5x + (1 - lnx)/2x^2

dy/dx = 5e^5x + (lne - lnx)/2x^2

dy/dx = 5e^5x + [ln(e/x)]/2x^2

Now, we'll determine the second derivative:

d^2y/dx^2 = [d[5e^5x + [ln(e/x)]/2x^2/dx

]In other words, we'll determine the derivative of the expression of the 1st derivative:

d^2y/dx^2= 25e^5x + {-2x^2/x - [1-ln(x]*4x}/4x^4

d^2y/dx^2 = 25e^5x - 2x(1+2-2lnx)/4x^4

d^2y/dx^2 = 25e^5x - 2x(1+2-2lnx)/4x^4

d^2y/dx^2 = 25e^5x - (1+2-2lnx)/2x^3

d^2y/dx^2 = 25e^5x - (3 - lnx^2)/2x^3

The second derivative is: d^2y/dx^2 = 25e^5x - (3 - lnx^2)/2x^3.

check Approved by eNotes Editorial